1984
DOI: 10.1007/bf00556885
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cardioselectivity and respiratory disease on pulmonary responsiveness to beta-blockade

Abstract: The effects on ventilation of the non-selective beta-blocker propranolol, and the relatively cardioselective beta-blocker, metoprolol, were compared in a randomized single-blind crossover study in 16 patients with asthma, bronchitis and emphysema (American Thoracic Society criteria). Group I had "fixed" airways disease with less than 20% improvement in FEV1 following inhaled salbutamol 5 mg by nebuliser. Group II had "reversible" obstruction, greater than 20% improvement. Bronchodilator therapy was withheld fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 26 publications
0
9
0
3
Order By: Relevance
“…Furthermore in the general population, FEV 1 increased in those who stopped taking β-blockers during the study. Other studies in patients with COPD report a fall in lung function and wheeze with propranolol and metoprolol 44 45. A study directly examining β-blocker tolerability in patients with concomitant heart disease and carefully documented airways disease, found that β-blockers were tolerated by 84% of the COPD patients (but only 50% with asthma) 46…”
Section: Theoretical and Clinical Study Concerns Of β-Blockers In Copdmentioning
confidence: 96%
“…Furthermore in the general population, FEV 1 increased in those who stopped taking β-blockers during the study. Other studies in patients with COPD report a fall in lung function and wheeze with propranolol and metoprolol 44 45. A study directly examining β-blocker tolerability in patients with concomitant heart disease and carefully documented airways disease, found that β-blockers were tolerated by 84% of the COPD patients (but only 50% with asthma) 46…”
Section: Theoretical and Clinical Study Concerns Of β-Blockers In Copdmentioning
confidence: 96%
“…The use of β blockers in patients with COPD has been a contentious issue since older generations of β blockers were shown to be intolerable by patients with obstructive airways disease, by precipitating bronchoconstriction [161], reducing FEV1, or lowering the methylcholine challenge threshold [162]. As a result, β blockers have been prescribed less to COPD patients, likely due to a concern that these side effects outweighed any cardiovascular benefit [11, 20, 21, 25].…”
Section: Impact Of Cardiac Medications On the Respiratory System Dmentioning
confidence: 99%
“…Metoprolol has been studied in varying doses in patients with asthma in at least 16 trials [17, 18, 26, 27, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40]. In virtually all of these studies, metoprolol caused some decrease in pulmonary function.…”
Section: Risks Of β-Blockers In Asthmamentioning
confidence: 99%
“…These authors also mentioned that 2 subjects with moderately severe asthma (not reported in the trial) had prolonged and severe bronchospasm associated with propranolol administration. Subsequent trials verified that nonspecific β-blockers should be avoided in patients with asthma [18, 26, 27, 28, 29, 30]. Table 1 offers examples of β 1 -blockers and nonspecific β-blockers.…”
Section: Risks Of β-Blockers In Asthmamentioning
confidence: 99%